Implications of external validity for research on polycentric and complex adaptive systems - Eric A. Coleman (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Much recent research has examined the implications of policy analysis for complex adaptive social-ecological systems. System complexity comes from both the natural environment as well as complex institutional arrangements that humans use to manage and regulate such systems. Such research has systematically investigated how the interaction of a host of variables relate to some evaluation criteria. Many scholars argue that a deep understanding of the social-ecological systems, however, comes at the expense of externally valid inferences to other systems. In this paper I argue that having a nuanced understanding of the social-ecological system actually helps one to understand which types of policy domains an analysis might be generalized.
Keywords: 330; Complex Adaptive Systems; External Validity; Polycentric Systems